Intraspecific Variation in Parental Care May Reflect Variation in Parental Quality - Natalie Pilakouta; Elizabeth J. H. Hanlon; Per T. Smiseth (Ecology and Evolution)
ABSTRACT The existence of life‐history trade‐offs is a fundamental assumption of evolutionary biology and behavioural ecology, yet empirical studies have found mixed evidence for this. Such trade‐offs are expected when individuals vary in how they allocate their limited resource budgets between different life‐history functions (variation in resource allocation), but they may be masked when individuals vary in how many resources they have acquired that they can later allocate to life‐history functions (variation in resource acquisition). We currently lack studies on the extent to which individual differences in behaviour reflect variation between individuals in resource acquisition and resource allocation. Here, we use parental care as a case study for exploring this question. We used the burying beetle Nicrophorus vespilloides, which exhibits facultative biparental care, comprising direct care (provisioning food or interacting with larvae) and indirect care (guarding or maintaining the carcass). We found some evidence for a positive relationship between these two components of care for both male and female parents. In addition, parents that spent more time providing care 24 h after hatching also tended to provide care for longer. Lastly, parents that provided more parental care did not experience a trade‐off of reduced lifespan after the breeding attempt. On the contrary, we found a positive relationship between the duration of care provided and parents' post‐breeding lifespan. Our finding of positive relationships between parental behaviours and between parental care and lifespan suggests that variation in care was mainly driven by differences in prior resource acquisition (i.e., parental quality) among individuals rather than differences in resource allocation. Our findings thus suggest that high intraspecific variation in parental quality can potentially mask reproductive investment trade‐offs within populations.